IMPLIKASI PEDAGOGIS AL-QUR’AN SURAT AT-TAUBAH AYAT 122 : (Analisis Kajian Tafsir Terhadap Kewajiban Belajar Mengajar) - Karnita Sarina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The Obligation to Learn to Teach according to the study of interpretation as human beings is to deepen religion and analysis knowledge, then practice and teach it to others and as educational objects or students are all Muslims, both himself and his family relatives and the people around him. Mufassir's interpretation of the Qur'an at-Taubah verse 122 is that in surah, it shows that the objects of education or students are some believers and the general public who have received instruction and teaching. The pedagogical implications of Al-Qur'an letter At-Taubah verse 122 concerning the obligation to learn and teach through the analysis of Tafsir Studies as a reference. Muslims should understand the division of tasks and roles of each so that they can benefit from one another in survival.